Teaching tools, techniques and strategies used by the teachers working in the pilot program "Compite", educational plan El Salvador 2021 developed by ITCA-FEPADE - Montes Durán, Sofía Carolina (Universidad de El Salvador, 2007)
English takes a very important role in this plan modification, which is named Plan El Salvador 2021, because inside this plan there is a pilot program named COMPITE that has been designed with the objective to form bilingual students by the year 2009. It is expected that students will be able to speak, read, or understand English very well and apply that knowledge in different labor areas (for example working for an International Hotel, restaurant, call center or promoting tourism), and in their everyday activities. This program is being developed by ITCA-FEPADE, which is an institution that the Ministry of Education has hired to carry out the program and which has taught English for several years in Santa Tecla city.